The Influence of the Source of Professional Standards on Juror Decision Making - Buckless, Frank A.; Peace, Robert L. (The Accounting Review, 1993)
[Auditor liability is a growing concern of public accounting firms (Collins 1985; Flynn et al. 1990; Mednick 1987; Minow 1984). In lawsuits brought by clients for breach of contract and tort actions for negligent execution of an audit, as well as in an increasing number of lawsuits brought by third parties, a common defense is the auditor's compliance with generally accepted auditing standards (GAAS). In this study, the source of professional auditing standards was manipulated to examine its influence on jurors' decisions. Four fact patterns were presented to members of jury pools called to jury duty. Prospective jurors responded to a fact pattern by voting in favor of either the plaintiff/client or the defendant/auditor. The fact patterns were manipulated to compare jurors' responses to standards of auditing performance established by the federal government versus those established by the auditing profession. In addition, a comparison was made of jurors' responses to two sets of instructions provided by the judge: either that standards alone set the required level of performance or that standards are only a part of the evidence to be considered in establishing the required level of performance. At trial, a judge's instructions to the jury before its deliberations can be influenced by counsel for the public accounting firm as to the evidentiary weight assigned to professional standards. The results that follow indicate that jurors are more likely to rule against a CPA firm when the profession's standards are offered in defense and less likely to rule against it when government standards of performance are offered in defense. Also, as expected, jurors are more likely to accept standards in defense, whether established by the government or the profession, if the judge identifies the standards as the only criterion for an expected level of performance rather than as only part of the evidence.]